Genomic analysis of "microphenotypes" in epilepsy. Issue 1 (27th September 2021) - Stanley, Kate; Hostyk, Joseph; Tran, Linh; Amengual‐Gual, Marta; Dugan, Patricia; Clark, Justice; Choi, Hyunmi; Tchapyjnikov, Dmitry; Perucca, Piero; Fernandes, Cecilia; Andrade, Danielle; Devinsky, Orrin; et al.
Abstract: Large international consortia examining the genomic architecture of the epilepsies focus on large diagnostic subgroupings such as "all focal epilepsy" and "all genetic generalized epilepsy". In addition, phenotypic data are generally entered into these large discovery databases in a unidirectional manner at one point in time only. However, there are many smaller phenotypic subgroupings in epilepsy, many of which may have unique genomic risk factors. Such a subgrouping or "microphenotype" may be defined as an uncommon or rare phenotype that is well recognized by epileptologists and the epilepsy community, and which may or may not be formally recognized within the International League Against Epilepsy classification system. Here we examine the genetic structure of a number of such microphenotypes and report in particular on two interesting clinical phenotypes, Jeavons syndrome and pediatric status epilepticus. Although no single gene reached exome‐wide statistical significance to be associated with any of the diagnostic categories, we observe enrichment of rare damaging variants in established epilepsy genes among Landau–Kleffner patients ( GRIN2A ) and pediatric status epilepticus patients ( MECP2, SCN1A, SCN2A, SCN8A ).